A High-Temperature Molecular Ferroelectric Zn/Dy Complex Exhibiting Single-Ion-Magnet Behavior and Lanthanide Luminescence - Long, Jerome
Multifunctional molecular ferroelectrics are exciting materials synthesized using molecular chemistry concepts, which may combine a spontaneous electrical polarization, switched upon applying an electric field, with another physical property. A high-temperature ferroelectric material is presented that is based on a chiral Zn2+/Dy3+ complex exhibiting Dy3+ luminescence, optical activity, and magnetism. We investigate the correlations between the electric polarization and the crystal structure as well as between the low-temperature magnetic slow relaxation and the optical properties.